UJI KEUNGGULAN CALON VARIETAS UNGGUL KACANG PANJANG (VIGNA SESQUIPEDALIS (L) FRUHW) DI DAERAH BLITAR - Soedomo, Rd. Prasodjo (JURNAL AGROTROPIKA, 2013)
Recently, yardlong bean trials were usually conducted in West Jawa. The rainfall of West Java is mostly higher than East Java. Blitar as one of production center of yardlong bean in East Java is estimated to be suitable for conducting the superior advantage test of yardlong beans (Vigna sesquipedalis (L) Fruhw) candidates. The objective of the trial was to test the superior line that has good adaptation in lowland area of yardlong bean production center in East Java with higher yield than control. The trial was conducted at Riawan Tani Station, Blitar, on latosol browness soil type, in Juni ? August 2012, using randomized block design with 8 treatments and 5 replications. The treatments were 5 lines from IVEGRI and 3 lines as control. The lines were:  (1) No. A.3/1630-CSL.19/200 (Pras-1), (2) No. A-8/1630-2489/2000 (Pras-2), (3) No. A-11/2316-2489/2000 (Pras-3), (4) No. A-4/DOA-1215/2000 (Pras-4), (5) DOA (Pras-5), (6) KP1 (releesed variety), (7) The local superior cultivar of Blitar and (8) Superior variety from Riawan Tani Company. The results showed that: (1) The breeding line of Pras 1, Pras 2 and Pras 3 had higher yield than control line (Kp 1, Local Blitar, and Riawan Tani), while Pras 4 and Pras 5 breeding line had similar yield as control; 2) The local Blitar performed the lowest yield and growth; (3) In the general the trial results on the superior advantage test had better yield and growth appearance than Priliminary Yield Test (PYT));  (4) Due to environmental factors,  conclusion of good lines by PYT were not exactly the same with those by the superior advantage test.  Key words : Vigna sesquipedalius lines, the superior advantage test, lowland